Detection of the Faraday Chiral Anisotropy - Venkatesan, Munuswamy; Coey, John (My University, 2021)
Being the intimate connection between chirality and magnetism, magneto-chiral anisotropies (MChA) - featuring non-reciprocal optical responses in chiral systems depending on the relative direction of the magnetic field B and the light propagation - have attracted much attention throughout the recent history of science1-3. The genuine two4-9 MChA phenomena are the so-called ‘pure’4-6,9 and ‘cascaded’7-9 effects. The ‘pure’ MChA phenomenon is proportional to the relative orientation between the wave vector of light k and B and has already been verified in numerous materials10-16 after its first observation in the late 20th century10. In marked contrast, the predicted ‘cascaded’ MChA effect remains unrevealed8,9,14. This intriguing ‘cascaded’ form of MChA is given by the simultaneous action of natural and magnetically induced optical activities in chiral systems and is the hallmark of bianisotropic electromagnetic materials generally referred to as Faraday chiral media17-21. Here, we report on the experimental observation of the elusive cascaded MChA and demonstrate its enantioselectivity. Corresponding electromagnetic simulations are in remarkable quantitative agreement with our measurements, which demonstrates the controllability of this phenomenon. The existence of this exotic effect is crucial in light-matter interactions, molecular spectroscopy and the design of novel metamaterials.
PUBLISHED
Keywords: Cascaded Magneto-Chiral Dichroism; Photonic crystals; Chiral nanomagnets; Faraday Chiral media; Metasurfaces; Complex electromagnetic media; Nanoscience & Materials; FABRICATION; NANOSTRUCTURES; Nanotechnology; Physics